SOCIAL INTERACTION PATTERNS OF SAMIN-ISLAMIC COMMUNITIES IN THE CONNECTION OF RELIGIOUS PEOPLE IN PATI DISTRICT - Nawa Syarif (INJECT (Interdisciplinary Journal of Communication), 2019)
The aim of this research is to know (1) pattern of social interaction in Samin community and Moslem, (2) some factors of interreligious harmony betwen Samin  community and Moslem in Baturejo village, (3) the efforts built by society of Baturejo to maintain interreligious harmony. The approach used in this research is phenomenology approach and the type of research used qualitative method. The main data sources are from Baturejo society. The techniques of collecting data by (1) interview, (2) observation, and (3) documentation. Data analysis by data reduction, data presentation, and conclusion. The result of this research indicate that the pattern of social interaction of the Samin community and Moslem in Baturejo village in the form of cooperation which is classified into three forms namely pattern of interaction in the economic, social, and religious fields. Some factors caused harmony are religious factor, cultural factor, and conflict factor. While the efforts made by society of Baturejo village to maintaining harmony are holding dialogue between residents,  together preserving culture, participating in enlivening the big day of other religious communities, never mentioning about religion and build form of family relation.